OPTIMALISASI ANALISIS SENTIMEN FILM PADA YOUTUBE DENGAN ALGORITMA CHI-SQUARE PADA NAÏVE BAYES DAN SUPPORT VECTOR MACHINE - Oky Kurnia Wardana; Alexius Endy Budianto; Moh Ahsan (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
The management of correspondence and monthly reports in educational administration environments still faces efficiency issues due to workflows that do not align with user needs and insufficient attention to usability aspects. These conditions result in suboptimal performance and low effectiveness in the use of digital systems. This study aims to analyze the usability of the web-based SIRATU application using the User-Centered Design (UCD) approach in accordance with the ISO 9241-210 standard. The research method includes analysis of the context of use, user identification, interface design, and usability evaluation using the System Usability Scale (SUS). The study is limited to the primary users of the SIRATU application, namely administrative staff, school operators, and the head of the district education office, with a focus solely on usability aspects. The evaluation results show an increase in the average SUS score from 60.6 to 87.4, which falls into the excellent category. The contribution of this study lies in the application of a UCD methodological framework that has proven effective in improving the usability of the SIRATU application.